Gaston Bachelard’s Philosophy of Scientific Method: from Breakthrough to Validation and its Applications in Contemporary Sciences - Allioua, Ali (Journal of Vasyl Stefanyk Precarpathian National University, 2025)
This article explores Gaston Bachelard's philosophy of the scientific method, focusing on the three main stages he proposes: epistemological rupture, knowledge construction, and empirical verification. We begin by analyzing Bachelard's concept of “epistemological rupture,” where he emphasizes that scientific progress requires a break from traditional knowledge and previous concepts. This rupture is seen as a critical step toward more accurate and advanced knowledge. We then move to the “construction” phase, where Bachelard stresses the importance of building scientific models and hypotheses through methodical and experimental thinking. This phase is crucial in the active and organized development of knowledge, free from initial assumptions. In the “verification” phase, we discuss the role of experimentation in validating the hypotheses and models that have been constructed. The role of experimentation varies between the natural and social sciences, and the article highlights how epistemological barriers can be overcome in the pursuit of scientific knowledge. Additionally, we address the application of Bachelard’s philosophy in contemporary sciences, both in physics and chemistry, as well as in social sciences, illustrating his impact on current scientific research practices. In conclusion, Bachelard’s philosophy sheds light on the process of scientific thought evolution, which is not just about the accumulation of knowledge but also requires constant reevaluation and critical revision of previous concepts. Bachelard's ideas remain an essential guide for understanding science in the modern era and serve as a foundation for pushing science toward new frontiers of understanding and discovery.